Physician associates in primary health care in England: A challenge to professional boundaries?. (May 2017) - Drennan, Vari M.; Gabe, Jonathon; Halter, Mary; de Lusignan, Simon; Levenson, Ros
Abstract: Like other health care systems, the National Health Service (NHS) in England has looked to new staffing configurations faced with medical staff shortages and rising costs. One solution has been to employ physician associates (PAs). PAs are trained in the medical model to assess, diagnose and commence treatment under the supervision of a physician. This paper explores the perceived effects on professional boundaries and relationships of introducing this completely new professional group. It draws on data from a study, completed in 2014, which examined the contribution of PAs working in general practice. Data were gathered at macro, meso and micro levels of the health care system. At the macro and meso level data were from policy documents, interviews with civil servants, senior members of national medical and nursing organisations, as well as regional level NHS managers (n = 25). At the micro level data came from interviews with General Practitioners, nurse practitioners and practice staff (n = 30) as well as observation of clinical and professional meetings. Analysis was both inductive and also framed by the existing theories of a dynamic system of professions. It is argued that professional boundaries become malleable and subject to negotiation at the micro level of service delivery. Stratification within professional groups created differing responses between those working at macro, meso and micro levels of the system; from acceptance to hostility in the face of a new and potentially competing, occupational group. Overarching this state agency was the requirement to underpin legislatively the shifts in jurisdictional boundaries, such as prescribing required for vertical substitution for some of the work of doctors. Highlights: Physician associates are a new profession within the English health care system. We investigated role boundaries and relationships at macro, meso and micro levels. At the micro level PAs substituted vertically and horizontally for others. Intra-profession stratification was evident in differing opinions to PAs. State agency i.e. legislation is needed for efficient vertical substitution.